Knowledge of Cervical Cancer, Human Papilloma Virus (HPV) and HPV Vaccination Among Women in Northeast China - Yu-e Ning; Yao Liu; Xiao-yu Xu; Xin-yu Zhang; Ning Wang; Li-qiang Zheng (Journal of Cancer Education, 2020)
This study aimed to research the understanding and knowledge of cervical cancer, human papilloma virus (HPV), and HPV vaccination, and the acceptance of HPV vaccination, among a population of women in northeastern China. A cross-sectional survey was carried out by questionnaire to investigate knowledge of cervical cancer, HPV, and HPV vaccination. The 230 female participants were native residents of northeastern China, and their ages ranged between 18 and 65 years. Questionnaires were randomly acquired by the respondents from online and paper questionnaire distribution. The questionnaire included questions on three major aspects to record people’s perceptions of cervical cancer, HPV, and vaccines. Of the sample of 230 women surveyed, 80.9% had heard of cervical cancer, but understanding was only 15.7%; 38.3% knew about HPV; 20% knew about HPV vaccine; 39.6% agreed to receive HPV vaccination, and the remainder were mainly concerned about its safety and effectiveness. Data analysis showed that age, family income, and whether there was experience of screening all influenced knowledge of cervical cancer, but this was not statistically significant. The level of education had no obvious effect on the degree of knowledge about cervical cancer; however, with an improvement in education, women’s awareness of HPV vaccine improved significantly ( p < 0.05). Women who have received cervical cancer screening had significantly greater knowledge about cervical cancer and HPV than those with no screening ( p < 0.05). Women in northeastern China have little knowledge of cervical cancer, HPV, and HPV vaccine, lack disease knowledge, and hold a skeptical attitude about HPV vaccination. Medical institutions are the main channel providing information to these women.

SNP of AHSA2 gene in three cattle breeds using snapshot technology - Shu-Zhu Cheng; E. Guang-Xin; Cheng-Li Liu; Wang-Dui Basang; Yan-Bin Zhu; Ri-Su Na; Yan-Guo Han; Yan Zeng; Xiao Wang; Wei-Wei Ni; Bai-Gao Yang; Xing-Hai Duan; et al. (Journal of Genetics, 2020)

PSD-93 Interacts with SynGAP and Promotes SynGAP Ubiquitination and Ischemic Brain Injury in Mice - Qingxiu Zhang; Hui Yang; Hong Gao; Xiaomei Liu; Qingjie Li; Rong Rong; Zhenqian Liu; Xiu-e Wei; Liping Kong; Yun Xu; Liangqun Rong (Translational Stroke Research, 2020)

Seasonal Rainfall Forecasts for the Yangtze River Basin of China in Summer 2019 from an Improved Climate Service - Philip E. Bett; Nicola Martin; Adam A. Scaife; Nick Dunstone; Gill M. Martin; Nicola Golding; Joanne Camp; Peiqun Zhang; Chris D. Hewitt; Leon Hermanson; Chaofan Li; Hong-Li Ren; et al. (Journal of Meteorological Research, 2020)

Noise does not equal bias in assessing the evolutionary history of the angiosperm flora of China: A response to Qian (2019) - Li‐Min Lu; Hai‐Hua Hu; Dan‐Xiao Peng; Bing Liu; Jian‐Fei Ye; Tuo Yang; Hong‐Lei Li; Miao Sun; Stephen A. Smith; Pamela S. Soltis; Douglas E. Soltis; Zhi‐Duan Chen (Journal of Biogeography, 2020)
In response to our paper on the evolutionary history of the Chinese flora, Qian suggests that certain features of the divergence time estimation employed might have led to biased conclusions in Lu et al (2018). Here, we consider Qian's specific criticisms, explore the extent of uncertainty in the data and demonstrate that (i) no systematic bias toward dates that are too young or too old is detected in Lu et al.; (ii) constraint of the crown age of angiosperms does not bias the generic ages estimated by Lu et al.; and (iii) ages derived from the Chinese regional phylogeny do not bias the conclusions reported by Lu et al. All these analyses confirm that the conclusions reported previously are robust. We argue that, like many large‐scale biodiversity analyses, sources of noise in divergence time estimation are to be expected, but these should not be confused with bias.

Molecular characterization of gut microbial shift in SD rats after death for 30 days - Huan Li; E. Yang; Siruo Zhang; Jing Zhang; Lu Yuan; Ruina Liu; Shakir Ullah; Qi Wang; Nosheen Mushtaq; Yi Shi; Cuihong An; Zhenyuan Wang; et al. (Archives of Microbiology, 2020)

Effect of Chinese Rice Wine on the Endogenous Protease Activity, Myofibrillar Degradation, and Quality Characteristics in Topmouth Culter ( Culter alburnus ) - Fan Wang; Jia-Liang He; Tursunay Turgun; Da-E Ge; Nurgul Rahman; Jian-Zhong Zhou; Xiao-Li Liu (Journal of Aquatic Food Product Technology, 2020)

Preparation, characterization, and antifungal evaluation of a new type of aminourea chitooligosaccharide derivatives - Jun Zhu; Song Liu; Yukun Qin; Rong’e Xing; Huahua Yu; Xiaolin Chen; Pengcheng Li (Journal of Oceanology and Limnology, 2020)

PI3K/Akt pathway is involved in the activation of RAW 264.7 cells induced by hydroxypropyltrimethyl ammonium chloride chitosan - Yue Yang; Rong’e Xing; Song Liu; Yukun Qin; Kecheng Li; Huahua Yu; Pengcheng Li (Journal of Oceanology and Limnology, 2020)

Mitogenomic phylogeny of the Naticidae (Gastropoda: Littorinimorpha) reveals monophyly of the Polinicinae - Hongyue Liu; Yi Yang; Shao'e Sun; Lingfeng Kong; Qi Li (Zoologica Scripta, 2020)
The Naticidae is a species‐rich family of predatory marine gastropods with substantial interspecific morphological diversity. The classification of the Naticidae has been traditionally based on morphology data, but the phylogenetic relationships within the family are debated due to conflicting molecular results, especially regarding the monophyly of subfamilies Polinicinae and Naticinae. To further resolve the phylogenetic controversies within the Naticidae, we undertake a phylogenetic approach using 14 newly sequenced complete or nearly complete (only lacking a control region) mitochondrial genomes. Both the maximum likelihood and Bayesian inference analyses supported monophyly of the Polinicinae, but paraphyly of the Naticinae due to the placement of the enigmatic genus Notocochlis . The ancestral character reconstruction suggests that the operculum, a character that currently defines the two subfamilies, evolved from an ancestor with a calcareous operculum in the evolutionary history of naticids. In addition, the chronogram estimates that naticids was originated in late Triassic (about 227 million years ago), consistent with previous hypotheses. Our study highlights the importance of using complete mitochondrial genomes while reconstructing phylogenetic relationships within the Naticidae. The evolution scenario of the naticid operculum contributes new insights into the classification of Naticidae.

Study of the closure temperature of (U-Th)/He in detrital zircon obtained from natural evolution samples - Chang’e Cai; Nansheng Qiu; Huili Li; Daniel F. Stockli; Jian Chang; Nian Liu (Science China Earth Sciences, 2020)

Arsenic Distribution, Accumulation and Tolerance Mechanisms of Typha angustifolia in Different Phenological Growth Stages - Guiying Yang; Huan Zhong; Xue Liu; Chang’e Liu; Shiyu Li; Lei Hou; Yungen Liu; Yan Wang; Wei Ren; Changqun Duan (Bulletin of Environmental Contamination and Toxicology, 2020)

Atmospheric mercury accumulation rate in northeastern China during the past 800 years as recorded by the sediments of Tianchi Crater Lake - Tao Zhan; Xin Zhou; Wenhan Cheng; Xiaoqing He; Luyao Tu; Xiaoyan Liu; Junyi Ge; Yuanyun Xie; Jun Zhang; Yongfa Ma; E Li; Yansong Qiao (Environmental Science and Pollution Research, 2020)

Methane production in the oxygenated water column of a perennially ice‐covered Antarctic lake - Wei Li; John E. Dore; August J. Steigmeyer; Yong‐Joon Cho; Ok‐Sun Kim; Yongqin Liu; Rachael M. Morgan‐Kiss; Mark L. Skidmore; John C. Priscu (Limnology and Oceanography, 2020)
Aerobic methane production in aquatic ecosystems impacts the global atmospheric budget of methane, but the extent, mechanism, and taxa responsible for producing this greenhouse gas are not fully understood. Lake Bonney (LB), a perennially ice‐covered Antarctic lake, has cold hypersaline waters underlying an oxygenated freshwater layer. We present temporal methane concentration profiles in LB indicating methane production in the oxygenated (> 200% air saturation) water. Experiments amended with methylphosphonate (MPn) yielded methane generation, suggesting in situ methanogenesis via the carbon‐phosphorus (C‐P) lyase pathway. Enrichment cultures from the lake were used to isolate five bacterial strains capable of generating methane when supplied with MPn as the sole P source. Based on 16S rRNA gene sequencing, the isolates belong to the Proteobacteria (closely related to Marinomonas , Hoeflea , and Marinobacter genera) and Bacteroidetes ( Algoriphagus genus). 16S rRNA metagenomic sequencing confirms the presence of these taxa in LB. None of the isolated species were reported to be capable to produce methane. In addition, orthologs of the phosphoenolpyruvate mutase gene ( PepM ) and methylphosphonate synthase ( MPnS ), enzymes involved in phosphonate and MPn biosynthesis, were widely spread in the LB shotgun metagenomic libraries; genes related to C‐P lyase pathways ( phn gene clusters) were also abundant. 16S rRNA and mcrA genes of anaerobic methanogens were absent in both 16S rRNA and metagenomics libraries. These data reveal that in situ aerobic biological methane production is likely a significant source of methane in LB.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.